2020
DOI: 10.1371/journal.pone.0239555
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of the inner retinal layer in the fellow eyes of patients with unilateral exudative age-related macular degeneration

Abstract: Objective To investigate the thicknesses of the ganglion cell-inner plexiform layer (GC-IPL) and retinal nerve fiber layer (RNFL) of the fellow eyes of patients with unilateral exudative age-related macular degeneration (AMD). Methods A total of 107 patients with unilateral exudative AMD [34 of typical choroidal neovascularization (tCNV), Group A; 73 of polypoidal choroidal vasculopathy (PCV), Group B] and 73 normal control eyes (Group C) were included. Drusen and subretinal drusenoid deposits were assessed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…The incidence of SDD in our cohort is very low and only found in the elderly group. It is reported that the incidence of SDD in PCV is 4.1%, which is considered as an independent risk factor for neovascularization [ 40 ], while the incidence of pachydrusen in PCV is 70% [ 41 ]. We believe that elderly cCSC patients with hyaline warts are more likely to develop PCV.…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of SDD in our cohort is very low and only found in the elderly group. It is reported that the incidence of SDD in PCV is 4.1%, which is considered as an independent risk factor for neovascularization [ 40 ], while the incidence of pachydrusen in PCV is 70% [ 41 ]. We believe that elderly cCSC patients with hyaline warts are more likely to develop PCV.…”
Section: Discussionmentioning
confidence: 99%
“…Thinning of the inner retinal structures has been reported for the retinal nerve fiber layer (RNFL), ganglion cell layer (GCL), inner plexiform layer (IPL), and ganglion cell complex (GCC) [ 9 , 10 , 11 , 12 ]. Suggested pathogenetic theories for inner retinal involvement are microvascular alterations with inner retinal ischemia and post-receptor trans-synaptic degeneration [ 1 , 6 , 7 , 11 , 13 , 14 ]. SDD are associated with both forms of late AMD, geographic atrophy and neovascularization [ 15 ].…”
Section: Introductionmentioning
confidence: 99%